2016
DOI: 10.3390/w8080319
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Means and Ends in Aquaculture Production—Part 1: The Functions

Abstract: Abstract:The aquaculture sector has been increasing its share in the total fish production in the world. Numerous studies have been published about aquaculture, introducing a variety of techniques and methods that have been applied or could be applied in aquaculture production systems. The purpose of this study is to present a systemic overview of the functions of aquaculture production systems. Each function of an aquaculture system is applied to carry out a certain purpose. The results are divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…This is done with a comprehensive literature review on the basis on of keywords generated in the previous work by Björnsdóttir et al [1]. The scope, execution of the literature review and the synthesis are described in the next couple of sections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is done with a comprehensive literature review on the basis on of keywords generated in the previous work by Björnsdóttir et al [1]. The scope, execution of the literature review and the synthesis are described in the next couple of sections.…”
Section: Methodsmentioning
confidence: 99%
“…The coverage of the article is limited to the functions identified by Björnsdóttir et al [1]. Only a general description of the technical solutions is given here.…”
Section: Scopementioning
confidence: 99%
See 1 more Smart Citation
“…The treatment functions are [3]: controlling temperature, solids, dissolved gasses (dissolved oxygen DO and CO 2 ), pH (along with alkalinity and hardness), N compounds, organic matter, P compounds, metals, disease outbreak along with the function of preventing diseases. The treatment function of controlling disease outbreak is out of the scope.…”
Section: The Taxonomy Of Technical Solutionsmentioning
confidence: 99%
“…In the previous three papers, the authors identified all of the possible functions needed in a aquaculture production system. They also list the key variables that have to be monitored and collected all of the methods that solve the functions [3]. One part of the functions, the treatments, were then analyzed and all technical solutions to each method categorized into a taxonomy of technical solutions [4,5].…”
Section: Introductionmentioning
confidence: 99%